The Democratic Conference and the Pre-Parliament in Russia, 1917: class, nationality, and the building of a postimperial community - Sablin, Ivan (Nationalities papers, 2023)
The article offers a detailed analysis of the debates at the All-Russian Democratic Conference and in the Provisional Council of the Russian Republic (the Pre-Parliament), which followed the proclamation of the republic on September 1, 1917, and predated the Bolshevik-led insurgency on October 25. The two assemblies were supposed to help resolve the multilayered political, economic, and military crises of the First World War and the Revolution by consolidating a Russian postimperial political community and establishing a solid government. The debates demonstrated that grievances and antagonism, which were articulated in terms of class and nationality, made the idea of a broad nationalist coalition unpopular, since it would halt agrarian and other reforms and continue the negligence of non-Russian groups. Furthermore, those who still called for all-Russian national or civic unity split on the issue of community-building. The top-down, homogenizing and bottom-up, composite approaches proved irreconcilable and precluded a compromise between non-socialist and moderate socialist groups. The two assemblies hence failed to ensure a peaceful continuation of the postimperial transformation and did not lead to a broad coalition against right and left radicalism. The divisions, which were articulated in the two assemblies, translated into the main rifts of the Russian Civil War.
Online-Veröffentlichung von Cambridge University Press: 22 November 2021
Gesehen am 24.06.2024